El Dorado Drive : a novel - Abbott, Megan, 1971- (G.P. Putnam Son's, 2025)
"When Harper moves in with her sister Pam, she's surprised to find Pam doing so well financially after her messy divorce. After all, Pam's ex-husband wiped their bank accounts, even stole from their kids. But Pam managed to find her way back. Thanks to the Wheel. Twice a month, the women of the Wheel meet. New members bring cash to the party that is pooled together and then gifted to one lucky member. It's all about giving back. Lifting each other up. As women should. As they must. But when Harper is invited, with the promise of an end to her financial burdens, the sisters inadvertently unleash a darkness lurking within the group. If they're not careful, it might just get them killed"--